Discriminated in Society and Marginalized in Media: Social Representation of Christian Sanitary Workers in Pakistan. (2nd January 2023) - Ittefaq, Muhammad; Ejaz, Waqas; Jamil, Sadia; Iqbal, Azhar; Arif, Rauf
ABSTRACT: Sanitary workers are globally marginalized both in media and society. Such discrimination is often amplified when such essential workers belong to a religious minority in Muslim majority societies such as Pakistan. Drawing from the frameworks of social representation and social identity theories, this study uses the qualitative method of in-depth interviews with 30 Christian sanitary workers to shed light on the perception of representation of Christian sanitary workers in Pakistan's mainstream media. Upon analyzing the data, three distinct themes emerge: (a) a lack of mainstream media representation, (b) excessive negative media representation, and (c) cognizance of the effects such representation yields. This investigation revealed that sanitary workers believe that they do not have any representation in Pakistan's mainstream media to voice their issues. Moreover, they have serious reservations about their polemic social representation and voice concerns regarding the media that often amplify such depictions. Despite being less educated, the respondents in the study appear to understand the influence of media in a democratic and multicultural society. Therefore, they expect traditional media to highlight their genuine issues (i.e., joblessness, health-related problems, and fair treatment in society), all of which, in their view, can make their life a lot easier.